USE OF SCALED SEMIVARIOGRAMS IN THE PLANNING SAMPLE OF SOIL CHEMICAL PROPERTIES IN SOUTHERN AMAZONAS, BRAZIL - Oliveira, Ivanildo Amorim De; Campos, Milton César Costa; Marques, José; Aquino, Renato Eleotério De; Teixeira, Daniel De Bortoli; Silva, Douglas Marcelo Pinheiro Da (Sociedade Brasileira de Ciência do Solo, 2015)
The lack of information concerning the variability of soil properties has been a major concern of researchers in the Amazon region. Thus, the aim of this study was to evaluate the spatial variability of soil chemical properties and determine minimal sampling density to characterize the variability of these properties in five environments located in the south of the State of Amazonas, Brazil. The five environments were archaeological dark earth (ADE), forest, pasture land, agroforestry operation, and sugarcane crop. Regular 70 × 70 m mesh grids were set up in these areas, with 64 sample points spaced at 10 m distance. Soil samples were collected at the 0.0-0.1 m depth. The chemical properties of pH in water, OM, P, K, Ca, Mg, H+Al, SB, CEC, and V were determined at these points. Data were analyzed by descriptive and geostatistical analyses. A large part of the data analyzed showed spatial dependence. Chemical properties were best fitted to the spherical model in almost all the environments evaluated, except for the sugarcane field with a better fit to the exponential model. ADE and sugarcane areas had greater heterogeneity of soil chemical properties, showing a greater range and higher sampling density; however, forest and agroforestry areas had less variability of chemical properties.

A escassez de informações sobre o comportamento espacial dos atributos dos solos na região amazônica tem sido preocupação de muitos pesquisadores. Assim, este trabalho teve como objetivos avaliar a variabilidade espacial de atributos químicos do solo e determinar a densidade amostral mínima para caracterizar a variabilidade desses atributos em cinco ambientes amazônicos. Este estudo foi realizado ao sul do Estado do Amazonas, em área com terra preta arqueológica (TPA), floresta, pastagem, agrofloresta e cana-de-açúcar. Nessas áreas, foram estabelecidas malhas de 70 × 70 m, com espaçamento regular de 10 m, totalizando 64 pontos em cada ambiente. Os solos foram coletados na profundidade de 0,0-0,10 m. Foram determinados os atributos químicos (pH em água, MO, P, K, Ca, Mg, H+Al, SB, CTC e V). Os dados foram analisados utilizando-se técnicas de estatística descritiva e geoestatística. Grande parte dos atributos estudados apresentou estrutura de dependência espacial. O modelo esférico foi o que melhor se ajustou aos atributos químicos nos diferentes ambientes, onde somente a cana-de-açúcar evidenciou melhor ajuste ao modelo exponencial. As áreas de TPA e cana-de-açúcar mostraram maior heterogeneidade dos atributos químicos do solo, apresentando menor alcance e maior densidade amostral, e a área com floresta e agrofloresta apresentaram menor variabilidade dos atributos químicos.
USO DE SEMIVARIOGRAMAS ESCALONADOS NO PLANEJAMENTO AMOSTRAL DE ATRIBUTOS QUÍMICOS DO SOLO EM AMBIENTES NA REGIÃO SUL DO AMAZONAS
Keywords: geostatistics; Amazonian soils; archaeological dark earth; sampling density; geoestatística; solos da Amazônia; terra preta arqueológica; densidade amostral